THE USE OF PSEUDO-CEREALS FLOURS IN BAKERY / UTILISATION DE FARINES DES PSEUDO-CEREALES DANS LA BOULANGERIE - ROMULUS MARIAN BURLUC; CAMELIA VIZIREANU; RODICA DINICA; FELICIA DIMA (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
Nowadays, a special attention should be given to the nutritional properties of foods. In the bakery industry there is a tendency to develop innovative range of bakery products by using the therapeutic role of cereals that are not used at their true potential (buckwheat, millet, rice, oats).